Views of Nigerian civil servants about compulsory COVID-19 vaccination: A qualitative study - Nyemike S. Awunor; Luret A. Lar; Alphonsus R. Isara (AOSIS, 2024)
Background: COVID-19 caused unforeseen global burden, although vaccine strategy rapidly stalled transmission and protected those at risk. Many governments made vaccination mandatory for public space access. Aim: This study aimed to elucidate perception of Nigerian civil servants towards mandatory COVID-19 vaccination and elicited their recommendations. Setting: This study was conducted in twelve purposively selected states in the six geopolitical zones and the Federal Capital Territory (FCT), Nigeria. Relevant ministries, departments and agencies were selected within the study sites. Methods: It was a qualitative study that interviewed consenting civil servants. Ethical approval was obtained from the National Health Research Ethics Committee. Interviews were conducted in person, following a pre-test. Data was analysed using NVivo software version 12. Results: Most participants were willing to take the vaccine if their safety was assured. However, enforcement to do so was a hindrance. Most participants commended the government for the effort to curb COVID-19 transmission and create awareness but were displeased with planning and handling of misconceptions. They recommended a more committed approach to vaccine production and funding by the government. Conclusion: Participants were willing to take the COVID-19 vaccines because the gains of protection outweighed the risks. They suggested a less involuntary approach through reinforcing awareness creation and avoiding threats. Contribution: There is limited qualitative research on perception of Nigerian civil servants regarding mandatory COVID-19 vaccination. Being the main driving force of Nigeria's public service, their views are invaluable. Findings could contribute to future policies in times of emergency.